AKTUALISASI PANCASILA: DARI GLOKALISASI KE TINDAKAN KOLEKTIF - Willfridus Demetrius Siga (Reformed Center for Religion and Society, 2018)
ABSTRACT: The millennial geration are considered to have active characters and to master technical and individual controls. This competency is often not balanced with the individual's ability to care about the problems of national ideology. The ideology in this matter is Pancasila which is still seen as a product of the past, intimidative and even turning into techniques of mass degradation. First, the author raises the thoughts of George Ritzer and Roland Robertson who mentioned that the authenticity of globalization must be firmly grounded in globalization. Second, the writer used Gabriel Marcel's perspective which offers a different approach to the millennial generation that lives in the digital revolution, the presence as a collective action. The intended action is a social action in which individuals are willing to take part through their presence that involves feelings and openness to the issue of nationalism so that Pancasila can be experienced as an ideology that is rich in collective values and habitus. KEYWORDS: ideology, pancasila, the millennial generation, techniques of mass degradation, globalization, glocalization, digital revolution, presence, collective action nationalism, values, habits